The Effect of Sleep Disorders on Anxiety and Depression in Health Workers: A Meta-Analysis - Alfiana Nur Rohmani; Bhisma Murti; Didik Gunawan Tamtomo (Journal of Epidemiology and Public Health, 2024)
Background: Sleep disorders are a clinical condition when a person frequently experiences problems or decreased sleep quality that can lead to anxiety and depression. The purpose of this meta-analysis is to estimate and analyze the magnitude of the influence of sleep disorders on anxiety and depression in health workers based on the results of previous similar primary studies.Subjects and Method: Meta-analysis was performed on a primary study with a cross-sectional design. The research with the PICO format is as follows. Q: Health workers. I: Sleep disturbances < 8 hours per day; C: No sleep disturbances (Enough sleep > 8 hours per day). O: Anxiety and depression. The meta-analysis study was conducted by searching for articles from databases in electronic form using Google schoolar and Pubmed. This study was conducted by researchers in November 2023 by searching and selecting research data online conducted by previous primary data researchers in Pubmed and google scholar with a research period of 2016-2023. The keywords used in the primary data search were "Mental health" OR "Anxiety" OR "Depression" AND "Sleep disturbance" AND "Health worker" OR "Healthcare". The inclusion criteria for this study are complete articles using Cross-sectional research, published years from 2013-2023. The analysis of the articles in this study uses RevMan 5.3 software.Results: The meta-analysis in this study included 7 cross-sectional studies from Hong Kong, China, Bangladesh, Saudi Arabia, the United States, and Turkey. The total sample size is 5,267 samples. The risk of anxiety caused by sleep disturbances in health workers was 1.6 times compared to health workers who did not experience sleep disturbances (aOR=1.67; CI 95%=1.05 to 2.45; p= 0.030). the risk of depression caused by sleep disturbances in health workers was 1.32 times compared to health workers who did not experience sleep disturbances (aOR=1.32; CI 95%=0.81 to 2.15; p= 0.270).Conclusion: Sleep disorders increase the risk of anxiety and depression in health workers.